Estrogen Signaling as a Therapeutic Target in Neurodevelopmental Disorders - Amanda Crider; Anilkumar Pillai (2016)
Estrogens, the primary female sex hormones, were originally characterized through their important role in sexual maturation and reproduction. However, recent studies have shown that estrogens play critical roles in a number of brain functions, including cognition, learning and memory, neurodevelopment, and adult neuroplasticity. A number of studies from both clinical as well as preclinical research suggest a protective role of estrogen in neurodevelopmental disorders including autism spectrum disorder (ASD) and schizophrenia. Alterations in the levels of estrogen receptors have been found in subjects with ASD or schizophrenia, and adjunctive estrogen therapy has been shown to be effective in enhancing the treatment of schizophrenia. This review summarizes the findings on the role of estrogen in the pathophysiology of neurodevelopmental disorders with a focus on ASD and schizophrenia. We also discuss the potential of estrogen as a therapeutic target in the above disorders.